The Influence of Personal Attitude and Perceived Behavioral Control on Entrepreneurial Intention: A Study of University Students in Dili, Timor-Leste - Reis, Domingas De Jesus Dos (JUSTBEST Journal of Sustainable Business and Management, 2024)
This study aims to identify the influence of Personal Attitude and Perceived Behavioral Control on Entrepreneurial Intention of students in Dili, Timor-Leste. Although entrepreneurship has great potential to develop the economy in Timor-Leste, the level of entrepreneurship among students is still relatively low. Therefore, it is important to understand the factors that influence their entrepreneurial intention. This study uses a quantitative approach with a descriptive correlational design and involves 83 students as a sample. Data were collected through a questionnaire measured with a 5-point Likert scale, which measures Personal Attitude, Perceived Behavioral Control, and Entrepreneurial Intention. The results of multiple linear regression analysis show that both variables, Personal Attitude and Perceived Behavioral Control, have a significant positive influence on Entrepreneurial Intention. Personal Attitude has a greater influence than Perceived Behavioral Control, but these two factors together explain about 42% of the variability in students' entrepreneurial intention. These findings suggest that developing positive attitudes towards entrepreneurship and empowering students with the skills and resources needed to address entrepreneurial challenges can increase entrepreneurial intentions among students in Timor-Leste.